Mixed culture microorganisms fermented soybean meal improves productive performance and intestinal health of Nile tilapia (Oreochromis niloticus) juveniles fed plant-based diets in a biofloc system - Picoli F.* (2022)
© 2022 John Wiley & Sons Ltd.This study aimed to evaluate the effect of plant-based diets containing different inclusion levels (7%, 14%, 21% and 28%) of mixed culture microorganisms fermented soybean meal (FSBM) on the zootechnical performance and intestinal health of juvenile Nile tilapia (Oreochromis niloticus) reared in a biofloc system. The FSBM diets were compared with a positive control diet with fish meal and a negative control diet with no animal protein. All diets were isoprotein (33% CP) and isoenergetic (4300 kcal GE/kg). The design was completely randomized with four replications and the experiment lasted 54 days. Juveniles (1.635 ± 0.198 g) were distributed in 24 tanks (70 L) at a density of seven animals per tank. Fermentation increased probiotic microorganisms count (lactic acid bacteria 4.75 ± 0.21 log CFU g−1 and yeast 3.30 ± 0.54 log CFU g−1) and improved nutritional characteristics of FSBM. In fish fed the diet containing 7% FSBM, growth performance did not differ from fish fed the fish meal diet. FSBM inclusion improved the food efficiency of plant-based diets. The inclusions above 21% of FSBM increased the intestinal villi height. In the inclusion of 28% of FSBM, the goblet cell was higher compared to that of the other plant-based diets. The inclusion of 7% FSBM allows a total replacement of fish meal without compromising the growth performance of the animals.